Motivation to CrossFit training: a narrative review - Matias T.S. (2020)
© 2020, Springer-Verlag Italia S.r.l., part of Springer Nature.Introduction: Considering the ongoing growth of CrossFit training, it is pertinent to examine the motivational characteristics of individuals who engage in this type of training modality. Purpose: This study aimed to examine the motivational characteristics displayed by individuals participating in CrossFit training through a narrative review. Methods: Four electronic databases (PubMed, SCOPUS, SPORTDiscus, and Web of Science) were searched from their inception to June 2019, with search criteria including terms related to motivation and exercise. We selected only original articles that investigated motivation among CrossFit training participants. Results: Fourteen studies met the inclusion criteria. The individuals’ motivation was mainly characterized by more autonomous forms of extrinsic motivation (identified and integrate regulations). The role of extrinsic motives is explained by the possibility of improving physical abilities/skills, health-related factors and well-being, and performance and competition affective responses. Compared with other forms of resistance training, motivational characteristics of individuals engaged in CrossFit training seem to be different, whereby those engaged in CrossFit training exude a high level of self-determination, and may experience a greater sense of satisfaction and pleasure. Conclusion: The present narrative review adds to the limited evidence related to CrossFit training and suggests that participation in CrossFit training is conducted with a great sense of belief and identify. Moreover, CrossFit training seems to provide inherent rewards, which may influence exercise adherence. Future studies should explore motivations and reasons as to why individuals dropout of participating in CrossFit training.